2016
DOI: 10.1021/acsami.6b02888
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Nanotubes-Adsorbed Electrospun PA66 Nanofiber Bundles with Improved Conductivity and Robust Flexibility

Abstract: Electrospun polyamide (PA) 66 nanofiber bundles with high conductivity, improved strength, and robust flexibility were successfully manufactured through simply adsorbing multiwall carbon nanotubes (MWNTs) on the surface of electrospun PA66 nanofibers. The highest electrical conductivity (0.2 S/cm) and tensile strength (103.3 MPa) were achieved for the bundles immersed in the suspension with 0.05 wt % MWNTs, indicating the formation of conductive network from adsorbed MWNTs on the surface of PA66 nanofibers. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
112
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 248 publications
(116 citation statements)
references
References 52 publications
3
112
0
1
Order By: Relevance
“…Popular examples of such nanoproducts are electrospun nanofibers and electrosprayed nanoparticles [13]. In these electrohydrodynamic methods, electrostatic energy performs a dominant function in generation; however, other energies, such as thermal, radiant, and mechanical energies, can be combined into the process for an effective production [46].…”
Section: Introductionmentioning
confidence: 99%
“…Popular examples of such nanoproducts are electrospun nanofibers and electrosprayed nanoparticles [13]. In these electrohydrodynamic methods, electrostatic energy performs a dominant function in generation; however, other energies, such as thermal, radiant, and mechanical energies, can be combined into the process for an effective production [46].…”
Section: Introductionmentioning
confidence: 99%
“…The SEM and FTIR results indicated that the flame‐retardant mechanism of DPPM in RPUF was the forming of intact and continuous char layer on the surface of RPUF in thermal degradation of the composite, which prevented the heat and mass transfer between the gas and the condensed phases and effectively protected the substrate material from burning. These flame retardants can be extended for multifunctional polymer nanocomposites with an aim to broaden the applications of inert polymers especially in the form states in the fields such as electromagnetic interference shielding, energy storage and other sensing applications …”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] The PAA adsorption strongly depended on the polymer size.…”
Section: Discussionmentioning
confidence: 99%